Liquid biopsy—from bench to bedside. (11th November 2022) - Ray, Amitava; Vohra, Tarang K
Abstract: Over the last decade, molecular markers have become an integral part in the management of Central Nervous System (CNS) tumors. Somatic mutations that identify and prognosticate tumors are also detected in the bio-fluids especially the serum and CSF; the sampling of which is known as liquid biopsy (LB). These tumor-derived biomarkers include plasma circulating tumor cells (CTCs), cell-free DNA (cf/ctDNAs), circulating cell-free microRNAs (cfmiRNAs), circulating extracellular vesicles, or exosomes (EVs), proteins, and tumor educated platelets. Established in the management of other malignancies, liquid biopsy is becoming an important tool in the management of CNS tumors as well. This review presents a snapshot of the current state of LB research its potential and the possible pitfalls.